Assessment of Sexual Dimorphism in Mandibular Ramus: An Orthopanoramic Study - Koju, S.; Maharjan, N.; Rajak, R. R. K.; Yadav, D. K.; Bajracharya, D.; Ojha, B. (Kathmandu University Medical Journal, 2021)
Background Mandible is the largest and strongest bone of the face, is very durable, and hence remains well preserved than many other bones. In cases of mass disasters where an intact skull is not found, the mandible may play a vital role in sex determination as it is the most dimorphic bone of the skull. Morphometric analysis of mandibular ramus provides highly accurate data to discriminate sex. This can be accomplished by the use of panoramic radiography which is widely available and is used routinely to assess the mandibular structures. Objective To evaluate and compare the various parameters of the mandibular ramus and to determine the usefulness of the mandibular ramus as an aid in sex determination. Method Orthopantomograms of 140 samples (70 males and 70 females) were collected from the archives and traced manually on matte acetate tracing paper. Various parameters of mandibular ramus were measured on the right and left sides. The obtained measurements were subjected to discriminant function analysis. Result Mandibular measurements on the right side were greater than on the left side. However, only the ramus breath (minimum and maximum) and projective height of ramus were statistically significant (p < 0.05). All the measurements were higher for males than females. F-statistic values indicated that the highest sexual dimorphism was seen with the projective height of ramus and least with minimum ramus breath. Conclusion Mandibular ramus measurements can be a useful tool for gender determination and can be an essential tool in forensic science especially when there is damaged or partially preserved mandibles and may be helpful for medico-legal purpose in Nepal.